2021
DOI: 10.1136/bmjopen-2021-053678
|View full text |Cite
|
Sign up to set email alerts
|

Participatory approaches in the development of health interventions for migrants: a systematic review

Abstract: ObjectiveAnalysis of participatory approaches to developing health interventions for migrants and how approaches embody core participatory principles of inclusivity and democracy.DesignA systematic review of original articles. Electronic searches within the databases MEDLINE, Embase, Global Health and PsychINFO (from inception—November 2020).Eligibility criteria for study selectionOriginal peer-reviewed articles reporting research to develop and implement a health intervention for migrants, incorporating parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 56 publications
(56 reference statements)
2
23
0
Order By: Relevance
“…To implement this kind of screening programme in the future, they will have to be adapted in accordance with GPs’ experiences and views, so that they reinforce a participatory research approach. 46 This could be achieved by expanding the qualitative study to migrants and other PHC stakeholders to obtain other relevant opinions. A policy brief could compile the final recommendations for PHC improvements.…”
Section: Discussionmentioning
confidence: 99%
“…To implement this kind of screening programme in the future, they will have to be adapted in accordance with GPs’ experiences and views, so that they reinforce a participatory research approach. 46 This could be achieved by expanding the qualitative study to migrants and other PHC stakeholders to obtain other relevant opinions. A policy brief could compile the final recommendations for PHC improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Participatory approaches can be employed for all study types and methods—qualitative, quantitative, mixed methods, trials and literature reviews [ 27 ] and to support development and implementation of interventions [ 22 , 38 ]. It can help combat research fatigue because of the importance it places on involving refugees and migrants in the identification of research priorities (Section 1 ) and the value of inter‐stakeholder, action‐oriented research (Section 2 ).…”
Section: Methodsmentioning
confidence: 99%
“… 33 A global systematic review of studies that used participatory approaches with migrants found important shortfalls, with few studies actively including migrants in all research stages, and generally poor reporting of how participatory research approaches were used and principles upheld. 40 …”
Section: Introductionmentioning
confidence: 99%